Manhaj al-Ṣuwar fī Taʿlīm al-Lughah al-ʿArabiyyah (Dirāsah al-Lughah al-ʿAṣabiyyah) - Moh Ismail (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Arabic has become one of the world's major languages, playing a significant role in international cultural, intellectual, economic, political, and communicative spheres. Consequently, language learning has emerged as an essential competency for contemporary generations and a key requirement for fostering mutual understanding and intercultural dialogue among diverse societies. As language education continues to evolve through advances in educational technology, innovative approaches are needed to improve the teaching and learning of Arabic for non-native speakers. Modern Arabic language instruction should be guided by internationally recognized pedagogical, technological, linguistic, and cultural standards, encompassing effective content delivery, digital learning resources, instructional strategies, and assessment methods to ensure quality, accessibility, and sustainability. This article presents an image-based approach to Arabic language teaching, highlighting the use of visual media as both an instructional tool and a teaching strategy to facilitate language acquisition and enhance learners' engagement and comprehension.